2019
DOI: 10.1007/s12035-019-01677-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Cerebrospinal Fluid BACE1 Species

Abstract: Background: The primary neuronal β-secretase in the brain is the β-site amyloid precursor protein cleaving enzyme 1 (BACE1). BACE1 is the main protease responsible for the amyloidogenic processing of the amyloid precursor protein (APP) leading to Aβ generation. Previous studies have suggested the potential of cerebrospinal fluid (CSF) β-secretase activity to be a diagnostic biomarker for Alzheimer's disease (AD), but these studies have not demonstrated consistent changes in AD CSF. Therefore, further biochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…It should be acknowledged, however, that several in vitro and animal data point to a non-linear relationship between the levels of gene expression and rates of enzyme activity that is highly influenced by post-translational modifications [55]. Indeed, experimental studies indicate that BACE1 activity significantly increases over time while its expression levels are less likely to be altered during cognitively healthy aging as well as in the presence of AD-related cognitive decline [3].…”
Section: Potential Explanation Of Controversial Results In Csf (And Bmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be acknowledged, however, that several in vitro and animal data point to a non-linear relationship between the levels of gene expression and rates of enzyme activity that is highly influenced by post-translational modifications [55]. Indeed, experimental studies indicate that BACE1 activity significantly increases over time while its expression levels are less likely to be altered during cognitively healthy aging as well as in the presence of AD-related cognitive decline [3].…”
Section: Potential Explanation Of Controversial Results In Csf (And Bmentioning
confidence: 99%
“…Moreover, recent research suggests that the existence of multiple enzyme isoforms could affect the correct estimation of BACE1 concentration. It is worth noting that some spliced forms do not have APPcleaving activity and that it is not known which (and whether) specific forms vary in AD [55]. The same study shows that other enzymes, detectable in CSF, such as cathepsin B, meprin β, and BACE2, could exert β-secretase activity.…”
Section: Methodological and Technological Challengesmentioning
confidence: 92%
“…LncRNAs are relatively stable, which indicates that the serum or CSF lncRNAs might be promising biomarkers and therapeutic targets for AD diagnosis and treatment (Table 1). The concentration of BACE1 in CSF and plasma shows a good diagnostic value in AD patients (Shen et al, 2018;Lopez-Font et al, 2019). Therapeutic strategies targeting BACE1 have been extensively developed but discontinued due to futility or safety reasons (Ghosh and Osswald, 2014;Hampel et al, 2021).…”
Section: Lncrna In Clinical Ad Management and Perspectivementioning
confidence: 99%
“…In this regard, BACE2 expression in human brain capillaries is higher than in neurons and higher than the expression of BACE1 (Yang et al, 2022). An early study indicated that, unlike BACE1, BACE2 activity was not related to Aβ concentration, and did not change significantly in the AD brain (Ahmed et al, 2010); but studies based on β‐secretase activity are problematic due to the large discrepancies in β‐secretase activity and expected BACE protein content (Lopez‐Font et al, 2019). More recently, by specifically analysing nuclei from brain vessels, it has been demonstrated that BACE2 mRNA levels are downregulated in cerebral vasculatures of AD patients (Yang et al, 2022).…”
mentioning
confidence: 99%